The Use of Code Mixing In Beauty Content Creators of Lula And Myra at Youtube Channels - Siti Fatimah Al Islamiah; Siti Aisyah (JournEEL, 2022)
ABSTRACT Sociolinguistics is a branch of linguistics that studies the relationship between language and society. Everyone has their own personal style of language when they communicate with others. In this study, the research investigated about code-mixing that found in YouTube Channels. The data is taken from the youtube channels of one beauty influencer named Lula and Myra. The aims of this study were to find out the types of code-mixing category used by Lula and Myra utterance in their videos. The researcher used Hoffman (1991) theory to reveal this study. The research applied qualitative descriptive method to analyze the types of code-mixing. The method of data collection is the researchers watched and written every utterance in the video and then categorized it into three characteristics of code mixing. The result of this research there are (7) intra-sentential mixing, (4) intra-lexical mixing, and (3) involving a change of pronunciation.